An Analysis Of Grammatical Errors In Writing Descriptive Text - Rohdearni Wati Sipayung; Benarita (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
Grammar error is one of the difficulties experienced by students in the writing process. This study conducted in order to investigate the grammatical errors in writing descriptive text made by the students of English Department of FKIP USI. This research aimed to know the grammatical errors that happen in writing class made by students of the second semester. In this study, the writer used Qualitative analysis, while the general pattern or the research design used by the researcher is a case study. This study found that the students make the grammatical error in writing descriptive text. Population taken in second semester of English student department. Purposive sampling is used in taking sample from the population. The researcher uses document papers as the instrument. The finding of this study showed that there are 6 types of grammatical error found namely: tenses, preposition, articles, voices, morphological, and verbs errors; the dominant grammatical error found is tense errors which has total occurrences of 75 (26.31%) specifically the use of past tense; the reason why students‟ made dominant error in using specifically past tense is the students‟ are lack of understanding the linguistic features of descriptive text. Based on the result, it is figured out that the students still have difficulties in applying grammatical structures in writing. In order to avoid the students in making another grammatical error, the researcher has suggested taking out remediation based on each problematic area of grammatical error categories